2022
DOI: 10.3389/fnut.2022.1025439
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal adiposity and appetite-regulating hormones in human milk are mediated through maternal circulating concentrations and might affect infant outcomes

Abstract: BackgroundAppetite-regulating hormones (ARH) in human milk (HM) are suggested to affect infants’ milk intake and possibly infant growth. Maternal adiposity might contribute to higher levels of ARH in HM, either from the mammary gland or from raised circulating levels due to higher adiposity. Counterfactual-based mediation analysis can define indirect and direct effects between HM ARH and maternal and infant factors, and might be an important tool when investigating the mother-milk-infant triad.ObjectiveWe aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Previous findings on this association have been unclear. Our results are consistent with other authors, 48,49 but on the other hand, a positive association with maternal BMI 18,19 and adiposity or fat mass 18,28,50 has also been reported. The association of plasma and milk insulin with infant growth has not been as extensively studied as for leptin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous findings on this association have been unclear. Our results are consistent with other authors, 48,49 but on the other hand, a positive association with maternal BMI 18,19 and adiposity or fat mass 18,28,50 has also been reported. The association of plasma and milk insulin with infant growth has not been as extensively studied as for leptin.…”
Section: Discussionsupporting
confidence: 93%
“…Human milk is a biological fluid characterized by a wide variation of metabolite and hormone contents. 14,15 The presence of leptin and insulin in milk is well documented, 16,17 their concentration correlates with maternal plasma levels [18][19][20] and varies depending on population characteristics and maternal lifestyle, diet and health status. 14,15 Insulin is believed to be actively transported into milk by mammary epithelial cells, 19,20 and leptin is produced in adipose tissue and mammary epithelial cells.…”
mentioning
confidence: 99%
“…The available data [86,89] indicate that adipokine concentrations might be related to milk maturation stages and, because of this, Ça giran Yilmaz and Özçelik [90] found a positive relationship between the first month milk leptin level and the mother's anthropometric measurements (weight and BMI), but not with the newborn's weight. Similar to our findings, other authors [91] did not find any associations between either milk leptin or adiponectin but found that maternal BMI was positively associated with milk leptin and insulin. Despite the fact that determinations of leptin and adiponectin levels in biological material are valuable, the leptin/adiponectin ratio has a higher diagnostic accuracy as a marker of insulin resistance and metabolic syndrome [92][93][94].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Jara et al [105] stated that even such a non-obvious factor as race affects adiponectin and leptin levels throughout pregnancy. Overall, appetite-regulating adipokines in human milk are suggested to affect newborn's and infants' milk intake and possibly offspring growth [91,106,107]. According to Adamska-Patruno and coworkers [108], the shift in the balance between serum ghrelin and other appetite-regulating hormones affects energy homeostasis [109][110][111].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation acts as a mediator between transient adverse environmental factors in early life and metabolic health risk in adulthood [103]. In humans, FABP4 has been shown to vary during lactation and shows strong correlations with adiponectin and leptin in breast milk [104], and maternal adiposity and breast milk composition may be linked to infant growth [105]. At the same time, weight trajectories in individuals with different polygenic risks for obesity start to diverge in early life [106], and the effects of an obesogenic environment on health are most pronounced in those with a genetic predisposition [106,107].…”
Section: Future Perspective On Fabp4 Researchmentioning
confidence: 99%